Kajian Tehnik Menggambar Wayang Beber Gaya Pacitan Joko Sri Yono - Gozali, Amir; -, Sutriyanto (Institut Seni Indoensia Surakarta, 2014)
This study aimed to Pacitan style wayang beber, which has the characteristics of a very complicated background and has a very interesting artistic value. Of the two also has a different procedure for the manufacture especially when applying the colors used. This study examines the anatomy of the body found in wayang beber, either the main character or some other supporting cast. Anatomy directed against members of the body found in various types of puppets such as the eyes, nose, mouth, ears, hands, feet up used clothing and accessories. In addition, this study will reveal some of the symbols contained in the background, where the background can be seen from the condition and location that is happening in each scene. In this study, the object is wayang beber with emphasis minitik studies on aspects of the art techniques and media apparently namely the manufacture of Pacitan style wayang beber Sri Yono Joko work. To solve some of the issues raised using a direct approach to the puppeteers, craftsmen and artists who are still there, especially Joko Sri Yono as an artist who holds the grip Pacitan style wayang beber, and a review of the existing literature. By using some of the theoretical approach is expected to answer the problem.Keywords: Wayang Beber, Style, Pacitan